Exploring Large Language Models in Gamified Environments : A Systematic Literature Review - Nurfauza, Jali; Lleyton, Geboh Leslie; Sadok, Ben Yahia; Wai Shiang, Cheah; Syahrul Nizam, Junaini (2025)
This systematic literature review (2020–2025) explores how the convergence of Large Language Models (LLMs), such as GPT-3.5, with gamification redefines traditional engagement paradigms. Unlike prior studies that examined LLMs and gamification separately, this review offers novel insights into their integration, highlighting how LLMs enable dynamic storytelling, realistic behavioural simulations, and adaptive user interactions that surpass static point-and-badge systems. A total of 718 articles from Scopus, IEEE Xplore, ScienceDirect, and ACM Digital Library were screened, with 27 meeting the inclusion criteria for detailed analysis. Key applications identified include intelligent non-player characters (NPCs), adaptive educational feedback, and embodied digital avatars for social simulations. While LLMs enhance personalisation and immersion, challenges such as content hallucination, ethical risks, and output inconsistency persist. This review provides a comprehensive synthesis of these opportunities and challenges, offering critical directions for researchers and designers to harness LLMs in gamified environments responsibly.